1972
DOI: 10.1002/neu.480030303
|View full text |Cite
|
Sign up to set email alerts
|

The flow of mitochondria in chicken sciatic nerve

Abstract: SUMMARYMitochondria1 flow in chicken sciatic nerve has been followed using [59Fe] as a marker for mitochondrial cytochromes.Radioactively labelled iron was injected into the ventral horn of the chicken spinal cord in the region of the cell bodies of the motor neurons, whose axons pass into the sciatic nerve. Protein-bound [59Fe] was found to move at a slow rate (1-4 mm/day) in the sciatic nerve. The total protein bound [jgFe] in the nerve reached a maximum at 9 days and then gradually diminished.The percentag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

1973
1973
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…The intra-axonal transport of mitochondria has previously been demonstrated in a number of systems (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). Although a few of these previous studies have suggested a relatively rapid movement of mitochondria (e.g., refs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The intra-axonal transport of mitochondria has previously been demonstrated in a number of systems (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). Although a few of these previous studies have suggested a relatively rapid movement of mitochondria (e.g., refs.…”
Section: Discussionmentioning
confidence: 99%
“…5 shows the arrival of group V polypeptides (those transported at a maximum velocity of 0.7-1.1 mm/day) [e.g., H(9),] 45, and 46 (2) in ON + OT by 16 days after the retina was labeled. Group V included material that was denser than mitochondria.…”
Section: Methodsmentioning
confidence: 99%
“…Verification of these issues needs quantitative analysis of in situ hybridization at the EM level. It is also possible that different levels of mitochondrial-encoded proteins may be caused by posttranslationally regulatory mechanisms, such as mitochondrial redistribution (Banks et al, 1969;Jeffrey et al, 1972;Morris and Hollenbeck, 1993). The greater consumption of energy in functionally active regions could lead to a local increase in ADP/ATP ratio, which can signal mitochondria to cease movement, resulting in clustering of mitochondria in regions of high ATP demand (Bereiter-Hahn and Voth, 1983).…”
Section: Factors Attributing To the Local Differential Levels Of Co Smentioning
confidence: 97%
“…Certain oxidative enzymes may be used as mitochondrial markers (Banks et al 1969;Partlow et al 1972), but the mitochondria of Schwann cells constitute by far the largest share of the total mitochondrial population of the nerve and they may, in addition, be altered by experimental techniques of ligature or of injury to the nerve. Isotopic tracers (Jeffery, James, Kidman, Richards & Austin 1972;Elam & Agranoff 1971), on the other hand, possess low specificity and may be subject to redistribution among other axoplasmic organelles upon release from mitochondria.…”
Section: Discussionmentioning
confidence: 99%